Early Lactate Clearance Rate is an Indicator of Outcome in Severe Sepsis and Septic Shock (BIRDEM Medical Journal, 2018)
Background: Lactate clearance is an important marker of global tissue hypoxia and might be used as an indicator of outcome in patients with severe sepsis and septic shock. This study was done to see the association between lactate clearance with the outcome of the patients of severe sepsis and septic shock among the patients who were admitted in the Department of Critical Care Medicine of BIRDEM General Hospital.Methods: This observational study was done in the Department of Critical Care Medicine, BIRDEM General Hospital from August 2015 to July 2016. At zero hour (during admission), first sample of serum lactate was sent and second sample after 6 hours of resuscitation for calculation of lactate clearance rate. Patients having lactate clearance e”10% were classified as high lactate clearance (HLC) and